2009
DOI: 10.1021/bi900626u
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Fibrillation of Human Apaf-1 CARD

Abstract: The idea of establishing the amyloid-like fibrillation tendency of pro- and antisurvival proteins of human apoptotic pathways is relevant for delineating the conditions that lead to aberrant differentiation, development, and tissue homeostasis. As the first step in this direction, we report here that the caspase recruitment domain (CARD) of recombinant human apoptotic protease activating factor-1 (Apaf-1) can be induced to undergo amyloid-like fibrillation. The study was initiated with a set of biophysical inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Specifically, we observed that activated caspase-7 partitions into DHR81 condensates, suggesting caspase sequestration as a potential antiapoptotic mechanism. Phase-separated condensates and higher-order assemblies are already implicated in mediating apoptosis: stress granules inhibit apoptosis by suppressing MAPK pathways; 48 the apoptosome relies on Apaf-1 multimerization, which has been reported to undergo amyloid fibrillation in specific conditions; 49 and stressdependent phase separation modulates proteasome formation, whose function affects apoptosis. 50,51 It is interesting to note that we only observe clear caspase-7 partitioning into DHR81 condensates, suggesting the possibility of a specific binding interaction in this case.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Specifically, we observed that activated caspase-7 partitions into DHR81 condensates, suggesting caspase sequestration as a potential antiapoptotic mechanism. Phase-separated condensates and higher-order assemblies are already implicated in mediating apoptosis: stress granules inhibit apoptosis by suppressing MAPK pathways; 48 the apoptosome relies on Apaf-1 multimerization, which has been reported to undergo amyloid fibrillation in specific conditions; 49 and stressdependent phase separation modulates proteasome formation, whose function affects apoptosis. 50,51 It is interesting to note that we only observe clear caspase-7 partitioning into DHR81 condensates, suggesting the possibility of a specific binding interaction in this case.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Interestingly, we observed that activated caspase-7 partitions into DHR81 condensates, suggesting caspase sequestration as a potential anti-apoptotic mechanism. Phaseseparated condensates and higher order assemblies are already implicated in mediating apoptosis: stress granules inhibit apoptosis by suppressing MAPK pathways (Arimoto et al, 2008); paraspeckles sequester pro-apoptotic tumor suppressors (Jiang et al, 2020); the apoptosome relies on Apaf-1 multimerization, which has been reported to undergo amyloid fibrillation in specific conditions (Rao et al, 2009); and stress-dependent phase separation modulates proteasome formation, whose function affects apoptosis (Gupta et al, 2018;Yasuda et al, 2020). It is interesting to note that we only observe clear caspase-7 partitioning into DHR81 condensates, suggesting the possibility of a specific binding interaction in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Apomyoglobin and myoglobin were induced to form amyloid fibrils similarly in 50 mM sodium borate (pH 9.0), low protein concentrations (1 mg/ml) and were incubated at 65 °C over 24 hours [16,27]. The Greek-key Apaf-1 CARD protein was shown to form fibrils in 50 mM glycine-HCl buffer (pH 2.0) incubated at 60 °C in a heating block [7]. Similarly, Fadd-DD forms fibrils under low pH conditions however deviations in temperature to 50 °C and the addition of NaCl for ionic strength and translational motion were required to overcome the stability of Fadd-DD and induce the fibrillar conformation Fig.…”
Section: Atomic Force and Transmission Electron Microscopymentioning
confidence: 99%
“…The elongation step is independent of initial fibril formation and has been shown to grow by the binding of monomeric protein to fibril extremities [6]. The process of *Address correspondence to this author at the Department of Chemistry and Biochemistry, Old Dominion University, 4541 Hampton Boulevard, Norfolk, VA 23529, USA; Tel: 757-683-6596; Fax: 757-683-4628; E-mail: lgreene@odu.edu forming amyloid fibrils in vitro typically involves incubating proteins or peptides under one or more extreme conditions such as elevated temperatures, acidic or basic pH, high ionic strength and mechanical agitation [7][8][9]. Thus, destabilization of the native state appears to be a pivotal step in the conversion process in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation